Generation Z Purchasing Decisions at Guar Coffee Shop on Jl. Seruni, Sumerta Kauh, East Denpasar District, Bali - Pratnyana, Dewa Kade Boga; Suastuti, Ni Luh; Juniari, Ni Kadek Eni (PT FORMOSA CENDEKIA GLOBAL, 2024)
Generation Z is currently fond of visiting the coffee shop of his choice. Guar Coffee is a coffee shop that is often visited by Generation Z today. Guar Coffee which comes with a modern and instagramable provides supporting facilities not to mention an affordable price. In this study, the data analysis technique used is descriptive quantitative, by entering the mean value into the class interval. The questionnaire consists of four question variables, in which there are variables of price, product, service quality, and promotion/marketing, where in each variable contains three indicators, the total of questions is 12 questions. The next step is to collect the questionnaires that have been filled out and tabulated, then enter the mean results into the interval class, after getting the average of all research variables that have been entered into the interval class, the data is analyzed, and converted into easy-to-understand sentences. Based on data analysis, overall it can be concluded that Generation Z agrees to make a purchase decision due to price, product, service quality, and promotion/marketing provided by the Guar Coffee shop on Jl. Seruni, Sumerta Kauh, East Denpasar District, Bali